2015
DOI: 10.1016/j.ijscr.2015.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic splenic tissues mimicking gastro-intestinal stromal tumour in a patient after splenectomy for a giant epithelial cyst of spleen: A case report

Abstract: HighlightsGiant epithelial splenic cyst is rare and splenectomy is the treatment.Auto-transplantation of ectopic splenic tissues during splenectomy may create diagnostic confusion when subsequent endoscopy or CT scan is performed years after the operation.99mTechnetium sulfur colloid scintigraphy is a useful adjunct and should be considered in doubtful cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Moreover, the explosive infection, the most dangerous complication, often occurs after splenectomy. As a result, the prognosis is poor and the patient's survival rate is low ( 7 ). With the deepening of the understanding of the spleen, it is found that retaining 25% spleen can maintain the normal function of the spleen, so minimally invasive treatment of retaining spleen is increasingly accepted, including partial splenic artery embolization and thermal ablation, but the former can easily lead to postoperative liver failure, splenic abscess, portal vein thrombosis, peritonitis and other complications ( 8 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the explosive infection, the most dangerous complication, often occurs after splenectomy. As a result, the prognosis is poor and the patient's survival rate is low ( 7 ). With the deepening of the understanding of the spleen, it is found that retaining 25% spleen can maintain the normal function of the spleen, so minimally invasive treatment of retaining spleen is increasingly accepted, including partial splenic artery embolization and thermal ablation, but the former can easily lead to postoperative liver failure, splenic abscess, portal vein thrombosis, peritonitis and other complications ( 8 11 ).…”
Section: Discussionmentioning
confidence: 99%